Hypoglycaemic effect of the methanolic extract of Aporusa lindleyana leaves on rats - Samanmali, B.L.C.; Gunatilake, Mangala; Guneratne, R.D.; Perera, T.R.K. (National Science Foundation of Sri Lanka, 2014)
Aporusa lindleyana is a medicinal plant, which is claimed to have a hypoglycaemic potential. This study was carried out to determine the hypoglycaemic effect, toxicity of long term usage and the phytochemistry of tender leaves of A. lindleyana. The hypoglycaemic effect of the methanolic leaf extract of A. lindleyana on the fasting and random blood glucose concentrations and the glucose tolerance were tested using three oral doses of the extract (100, 400, 800 mg/kg) in Sprague-Dawley rats. Sub-acute toxicity studies were performed after treating the rats for 28 consecutive days with the highest dose and were tested for different parameters. The results exhibit a dose dependent hypoglycaemic effect with the maximum blood glucose reduction observed at the 4th hour after the treatment. All three tested doses significantly reduced the fasting blood glucose concentration 4 hours after treatment. Only the intermediate and the highest doses showed a significant reduction in random blood glucose concentration in normoglycaemic non-fasted rats and a significant glucose tolerance, when tested on an oral glucose load. There was no significant difference in the physical and biochemical parameters in rats treated with the extract for 28 days compared to the control group. The extract contained alkaloids, saponins, flavonoids and leucoanthocyanins as revealed by phytochemical screening. It can be concluded that A. lindleyana leaves exhibit hypoglycaemic activity since they significantly (p < 0.05) reduce the blood glucose concentration in normoglycaemic rats and significantly (p < 0.05) enhances the glucose tolerance. The long term use of the leaf extract does not produce any toxic signs in rats.
Keywords: Aporusa lindleyana; blood glucose concentration; diabetes mellitus; hypoglycaemic effect; toxicity